Crisis communication strategies prepare, respond and recover effectively in unpredictable and urgent situations - Coleman, Amanda (Kogan Page, 2023)
Is your company equipped to deal with any kind of crisis - whether caused by internal error, customer action or social media mishap? This bestselling guide gives readers the skills, tools and knowledge to respond effectively to these high-stake situations and protect your brand from disaster. Crisis Communication Strategies is a must-have guide that covers the whole span of a crisis from preparing and laying the groundwork before it occurs, during the incident, and the aftermath, including the move to recovery and beyond. It guides readers through each phase, providing details of what to consider, what should be done and tips and checklists for improved responses. This second edition of Crisis Communication Strategies provides new sections on managing long-running crises and the phases of crises. It also contains new content looking at behavioral communication as a tactic during a crisis, and how to ensure diversity and inclusivity at a time of crisis. Supported by brand new case studies and examples from responses to events including the British Post Office scandal, Burger King's misfired International Women's Day campaign, Yorkshire cricket's racism scandal and Peloton's crises. It also explores the role of leadership in a crisis and developing a crisis communication response that has people at the heart of it. It is an essential guide for PR and communication professionals who wish to protect their company and build long-term resilience"--